The effect of green tea extract supplementation on exercise-induced oxidative stress parameters in male sprinters - Jówko, Ewa (Eur J Nutr, 2014)
BACKGROUND: Although research suggests that antioxidant supplementation can protect against exercise-induced muscle damage and oxidative stress, also delayed post-exercise muscle recovery and hindered adaptation to training were reported in the supplemented athletes. PURPOSE: The purpose of the study was to evaluate the effects of green tea extract (GTE) supplementation on selected blood markers of oxidative stress and muscle damage in sprinters during preparatory phase of their training cycle. METHODS: Sixteen sprinters participated in a double-blind, randomized, placebo (PL)-controlled crossover study, including two 4-week treatment periods with PL and GTE (980 mg polyphenols daily). The sprinters performed two repeated cycle sprint tests (RST; 4 × 15 s, with 1-min rest intervals), after PL and GTE supplementation. Blood was sampled before (at rest), 5 min after RST, and after the 24-h recovery. The activities of superoxide dismutase (SOD) and glutathione peroxidase were measured in erythrocytes, and total polyphenols, total antioxidant capacity (TAC), uric acid (UA), albumin (AL), malondialdehyde (MDA), and creatine kinase (CK) were determined in blood plasma. RESULTS: Repeated cycle sprint test performed after PL induced an increase in MDA, TAC, and SOD. Moreover, an increase in UA, AL, and CK was observed after RST irrespective of experimental conditions (PL, GTE). Supplementation with GTE caused an increase in total polyphenols and TAC at rest, and a decrease in MDA and SOD after RST. No significant changes in sprint performance were noted after GTE, as compared to PL. CONCLUSIONS: Supplementation with GTE prevents oxidative stress induced by RST in sprinters. Furthermore, GTE supplementation does not seem to hinder training adaptation in antioxidant enzyme system. On the other hand, neither prevention of exercise-induced muscle damage, nor an improvement in sprint performance is noted after GTE administration.